Sosialisasi Penyuluhan Upaya Peningkatan Perlindungan Hak Anak Buah Kapal (ABK) dan Implementasinya - Kamsariaty, Kamsariaty (PT. Sharia Journal and Education Center, 2024)
Abstract This study aimed to evaluate the efforts of socialization and counseling in enhancing the protection of the rights of crew members (ABK) and their implementation in the field. Crew members often face various challenges related to the protection of their rights, including unsafe working conditions, excessive working hours, and unfair treatment. Through structured socialization and counseling, it is expected that there will be an increase in awareness and understanding of the rights of the crew members. The results of this community service activity have shown that regular socialization and counseling programs have successfully increased understanding of the rights of crew members and reduced the number of rights violations in the shipping sector. However, there are still challenges in implementing regulations in the field, requiring further collaboration between the government, ship owners, and non-governmental organizations to ensure that the rights of crew members are well protected. In conclusion, improving the protection of the rights of crew members requires a holistic approach involving various stakeholders in its implementation. Keywords: Rights protection, crew members, socialization, counseling, implementation, workers' rights. Abstrak Dalam Pelaksanaanya telah bertujuan untuk mengevaluasi upaya sosialisasi dan penyuluhan dalam meningkatkan perlindungan hak-hak Anak Buah Kapal (ABK) serta implementasinya di lapangan. ABK sering kali menghadapi berbagai tantangan terkait perlindungan hak, termasuk kondisi kerja yang tidak aman, jam kerja yang berlebihan, dan perlakuan yang tidak adil. Melalui sosialisasi dan penyuluhan yang terstruktur, diharapkan peningkatan kesadaran dan pemahaman mengenai hak-hak ABK dapat tercapai. Hasil pengabdian kepada Masyarakat ini telah menunjukkan bahwa program sosialisasi dan penyuluhan yang dilakukan secara berkala telah berhasil meningkatkan pemahaman tentang hak-hak ABK dan mengurangi jumlah kasus pelanggaran hak di sektor perkapalan. Namun, masih terdapat tantangan dalam penerapan peraturan di lapangan, yang membutuhkan kolaborasi lebih lanjut antara pemerintah, pemilik kapal, dan organisasi non-pemerintah untuk memastikan hak-hak ABK terlindungi dengan baik. Kesimpulannya, peningkatan perlindungan hak ABK memerlukan pendekatan holistik yang melibatkan berbagai pemangku kepentingan dalam penerapannya. Kata Kunci: Perlindungan hak, Anak Buah Kapal, sosialisasi, penyuluhan, implementasi, hak pekerja.